2004
DOI: 10.1159/000080717
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Spectrum Disorder: A Pilot Study

Abstract: Objective: To assess depressive features of a proposed definition of bipolar spectrum disorder (BSD). Methods: Thirty-six patients with bipolar disorder type I or II were compared to 37 patients with unipolar major depressive disorder through patient interview and chart review. Results: Univariate analysis suggests that 7 of 12 (recurrent major depressive episodes, brief major depressive episodes, atypical depressive symptoms, early age of onset, family history of bipolar disorder, antidepressant tolerance, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 18 publications
0
22
0
2
Order By: Relevance
“…Specifically, among those women given a diagnosis of unipolar depression upon first presentation, women who presented in the postpartum period had a relative risk of 2.88 (95% CI 1.51–5.92) of a subsequent BPD diagnosis, compared to women presenting at any other time. Another study that compared depressive symptoms in BPD patients to unipolar patients found a greatly increased reporting of a postpartum episode in BPD patients compared to unipolar (OR = 7.9 95% CI 0.8 – 378.1)(Ghaemi et al, 2004). However, the small sample size of the study meant that the null hypothesis of equality of postpartum episodes could not be rejected.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, among those women given a diagnosis of unipolar depression upon first presentation, women who presented in the postpartum period had a relative risk of 2.88 (95% CI 1.51–5.92) of a subsequent BPD diagnosis, compared to women presenting at any other time. Another study that compared depressive symptoms in BPD patients to unipolar patients found a greatly increased reporting of a postpartum episode in BPD patients compared to unipolar (OR = 7.9 95% CI 0.8 – 378.1)(Ghaemi et al, 2004). However, the small sample size of the study meant that the null hypothesis of equality of postpartum episodes could not be rejected.…”
Section: Discussionmentioning
confidence: 99%
“…Bunlar arasında erken yaşta başlangıç, bipolar bozukluk yönünden pozitif aile öyküsü, atipik belirtiler, psikotik bulgu, yineleyici ve kısa depresyonlar, postpartum başlangıç, hipertimik mizaç, antidepresan toleransı ya da yanıtsızlık, manik kayma sayılabilir. [42] Hem tanı alana dek geçen süreyi uzatması hem de önceki yanlış tanı oranını arttırması yönünden bir diğer risk, hipomanik atakların atlanması, atlanmadığı yerde de geriye dönük tanılandırmanın güvenilirliğinin düşüklüğüdür. Bu engel ve kısıtlılığı ortadan kaldırmaya yönelik önlem ve öneri, hipomaninin bir ölçüm aracı ile taranması ve gelecek tanılandırma sistemlerinde duygudurum yerine psikomotor aktivite ölçütlerine ağırlık verilmesidir.…”
Section: Başlangıç Yaşı Ve Tanıunclassified
“…Thus, several neuropsychiatric disorders are expressed by the penchance for immediate gratification of ongoing desire at the expense of long-term considerations and are thereby characterised by a lack of proficiency in decision-making and impulsive choice behaviour (cf., First et al, 1996;Bulik et al, 1997;Soloff et al, 2000;Mitchell et al, 2002;Swann et al, 2004;2005;2007). In this regard, bipolar disorder, a highly debilitating condition (Murray and Lopez, 1996), with serious suicide risk (Baldessarini and Tondo, 2003) and, in particular, diagnostic dilemma (Manning, 2003;Ghaemi et al, 2004;Bowden, 2005;Swann, 2006). Nevertheless, there exists a plethora of evidence for functional abnormality in several brain regions, including the amygdala, anterior cingulate cortex, striatum, hippocampus and, in the context of impulsive behaviour , the dorsolateral prefrontal cortex (Altshuler et al, 1998;Adler et al, 2004;Gruber et al, 2004;Lawrence et al, 2004;Blumberg et al, 2005;Malhi et al, 2005Malhi et al, , 2007Lapopoulis et al, 2007;Wessa et al, 2007).…”
Section: Impulsiveness In Depressive Statesmentioning
confidence: 99%